Phylogenomic Evidence Overturns Current Conceptions of Social Evolution in Wasps (Vespidae) - Piekarski, Patrick K; Carpenter, James M; Lemmon, Alan R; Moriarty Lemmon, Emily; Sharanowski, Barbara J (Molecular biology and evolution, 2018)
The hypothesis that eusociality originated once in Vespidae has shaped interpretation of social evolution for decades and has driven the supposition that preimaginal morphophysiological differences between castes were absent at the outset of eusociality. Many researchers also consider casteless nest-sharing an antecedent to eusociality. Together, these ideas endorse a stepwise progression of social evolution in wasps (solitary → casteless nest-sharing → eusociality with rudimentary behavioral castes → eusociality with preimaginal caste-biasing (PCB) → morphologically differentiated castes). Here, we infer the phylogeny of Vespidae using sequence data generated via anchored hybrid enrichment from 378 loci across 136 vespid species and perform ancestral state reconstructions to test whether rudimentary and monomorphic castes characterized the initial stages of eusocial evolution. Our results reject the single origin of eusociality hypothesis, contest the supposition that eusociality emerged from a casteless nest-sharing ancestor, and suggest that eusociality in Polistinae + Vespinae began with castes having morphological differences. An abrupt appearance of castes with ontogenetically established morphophysiological differences conflicts with the current conception of stepwise social evolution and suggests that the climb up the ladder of sociality does not occur through sequential mutation. Phenotypic plasticity and standing genetic variation could explain how cooperative brood care evolved in concert with nest-sharing and how morphologically dissimilar castes arose without a rudimentary intermediate. Furthermore, PCB at the outset of eusociality implicates a subsocial route to eusociality in Polistinae + Vespinae, emphasizing the role of mother-daughter interactions and subfertility (i.e. the cost component of kin selection) in the origin of workers.